What should be subtracted from -7mn + 2m² + 3n² to get m² + 2mn + n²
Solution:
We need to subtract a suitable term from the given expression -7mn + 2m² + 3n² to get m² + 2mn + n².
Let the term to be subtracted be N.
Now, -7mn + 2m² + 3n² - N = m² + 2mn + n²
On rearranging,
-7mn + 2m² + 3n² = m² + 2mn + n² + N
By combining like terms,
N = -7mn + 2m² + 3n² - (m² + 2mn + n²)
N = -7mn + 2m² + 3n² - m² - 2mn - n²
N = -7mn - 2mn + 2m² - m² + 3n² - n²
N = (-7 - 2)mn + (2 - 1)m² + (3 - 1)n²
N = (-9)mn + (1)m² + (2)n²
Therefore, N = -9mn + m² + 2n²
✦ Try This: What should be subtracted from 3x³ - 7x²y + 3xy² + 5y³ to get 2x³ - 3x²y + 4xy² + 2y³
☛ Also Check: NCERT Solutions for Class 7 Maths Chapter 12
NCERT Exemplar Class 7 Maths Chapter 10 Problem 60 (b)
What should be subtracted from -7mn + 2m² + 3n² to get m² + 2mn + n²
Summary:
-9mn + m² + 2n² should be subtracted from -7mn + 2m² + 3n² to get m² + 2mn + n²
☛ Related Questions:
visual curriculum